(untitled) (Journal of Foreign Language Studies, 2025)
This study proposes an improved approach to teaching reading comprehension to secondyear Japanese-majored students at Hanoi University, drawing on the CEFR framework and relevant prior research. Data were collected through an analysis of the C1-level textbook and surveys with both teachers and students. The findings indicate that while the textbook offer texts of diverse topics and pedagogical activities with a focus on speed and intensive reading, students encounter many difficulties in interactive reading lessons. These include limited acquisition of complex vocabulary and kanji, struggles with advanced grammar, challenges in grasping text content, and the lack of self-study skills without teacher guidance. To address these issues, this study proposes a three-stage reading model (pre-, while-, and post-reading) that flexibly combines reading strategies. Its effectiveness was confirmed through a five-week experimental implemantation: students‘ test scores were improved significantly, and most of them found the new model engaging and effective.